HUBUNGAN KEPERDATAAN ANAK DI LUAR NIKAH PERSPEKTIF SEJARAH SOSIAL HUKUM ISLAM - Moch. Nurcholis; Muhammad Iqbal (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2021)
In Indonesia, children out of wedlock are only related to their mothers. This can be seen in Article 46 UUP. No.1 of 1974 and Article 99 of the KHI. The rules are presumably still based on the classical fiqh understanding of the termination of the lineage of children out of wedlock. Then the Constitutional Court made a decision that the child also has a civil relationship with his biological father. From this problem, two questions arise. First, how is lineage in Islamic law?. Second, how is the civil relationship between children out of wedlock from the perspective of the Social History of Islamic Law? When viewed from the focus of the study, this article includes historical-analytical research. When viewed from the operational data collection studied, this research is a library research. Primary and secondary data were analyzed using descriptive analysis method, by processing the study of the social history of Islamic law to find the meaning of civil relations. The approach used is a historical approach, which describes social phenomena in the past then drawn to the present to become more relevant. There are two research results: first, Based on the analysis, nasab which has been sacred, by some people it turns out that along with the development of the nasab era turned out to still be a difference among scholars with social development. Second, in the perspective of the Social History of Islamic Law, the Constitutional Court's decision regarding the civil relationship of children out of wedlock means the rights that exist within the lineage itself.